Knowledge about Conjunctivitis among School Students in Pokhara Metropolitan City - Sharma, Sharada; Thapa, Shital (Kalika Journal of Multidisciplinary Studies, 2025)
Conjunctivitis is a common and frequently observed health problem worldwide. It is highly contagious that makes school environment conducive for the transmission. The main objective of the study is to assess knowledge on conjunctivitis among school students of Pokhara. A descriptive cross-sectional study was conducted among selected three government schools in Pokhara Metropolitan City. Multistage sampling technique was used to select the schools and complete enumeration was done to collect data from selected schools. The total number of students included in the study was 268. Self-administered structured questionnaire was used to collect data. The collected data was entered in SPSS for analysis. The data was analyzed using descriptive statistics like frequency, percentage, mean, standard deviation. Inferential statistics chi-square test was used to identify the association between level of knowledge and selected variables. The study showed that 1.5 percent had good, 6.3 percent had moderate and 33.8 percent had poor level of knowledge on conjunctivitis. There was significant association between the age and information from school (p =<0.01) with level of knowledge. The study concluded that most of the students had a moderate level of knowledge on conjunctivitis. A significant association was observed between age and information form school with level of knowledge. Hence, health education program/ awareness campaign should be conducted in the school to promote level of knowledge on conjunctivitis as it is the most common eye problem worldwide.